1. x = 4, y = 3
2. Infinite solutions (The two equations are the same)
3. x = -6, y = -4
4. x = -135, y = -101.25
5. One solution
1. Solve the system of two linear equations.
-3x - 4y = -23
3x - 5y = 5
2. How many solutions does the system of equations have?
8x - 6y = 48
8x + 6y = 48
3. Solve the system of two equations using elimination with multiplication.
4x - 6y = -48
-2x + 4y = 30
4. Solve the system of two equations.
3x - 4y = 40
5x - 5y = 55
5. How many solutions does the system have?
12x - 15y = 18
4x - 5y = 6
……
11 answers
Number one is wrong
I apologize for that mistake. Let's re-calculate the first problem:
1. Solve the system of two linear equations.
-3x - 4y = -23
3x - 5y = 5
Adding the two equations together to eliminate x:
-3x - 4y + 3x - 5y = -23 + 5
-y = -18
y = 18
Substitute y back into the first equation:
-3x - 4(18) = -23
-3x - 72 = -23
-3x = 49
x = -49/3
Therefore, the solution to the system of equations is x = -49/3, y = 18.
1. Solve the system of two linear equations.
-3x - 4y = -23
3x - 5y = 5
Adding the two equations together to eliminate x:
-3x - 4y + 3x - 5y = -23 + 5
-y = -18
y = 18
Substitute y back into the first equation:
-3x - 4(18) = -23
-3x - 72 = -23
-3x = 49
x = -49/3
Therefore, the solution to the system of equations is x = -49/3, y = 18.
Try again
I apologize for the mistake. Let's re-calculate the first problem again:
1. Solve the system of two linear equations.
-3x - 4y = -23
3x - 5y = 5
From the second equation, rearrange it to solve for x:
3x = 5 + 5y
x = (5 + 5y) / 3
Substitute x into the first equation:
-3((5 + 5y) / 3) - 4y = -23
-5 - 5y - 4y = -23
-9y = -18
y = 2
Now, substitute y back into the second equation:
3x - 5(2) = 5
3x - 10 = 5
3x = 15
x = 5
Therefore, the solution to the system of equations is x = 5, y = 2.
1. Solve the system of two linear equations.
-3x - 4y = -23
3x - 5y = 5
From the second equation, rearrange it to solve for x:
3x = 5 + 5y
x = (5 + 5y) / 3
Substitute x into the first equation:
-3((5 + 5y) / 3) - 4y = -23
-5 - 5y - 4y = -23
-9y = -18
y = 2
Now, substitute y back into the second equation:
3x - 5(2) = 5
3x - 10 = 5
3x = 15
x = 5
Therefore, the solution to the system of equations is x = 5, y = 2.
Number 3 is wrong
Let's re-calculate the third problem using elimination with multiplication:
3. Solve the system of two equations using elimination with multiplication.
4x - 6y = -48
-2x + 4y = 30
Multiply the second equation by 2 to eliminate x:
8x - 12y = -96
-2x + 4y = 30
Now, add the two equations:
8x - 12y + (-2x + 4y) = -96 + 30
6x - 8y = -66
Divide by 2 to simplify:
3x - 4y = -33
Now we have a new equation:
3x - 4y = -33
4x - 6y = -48
Multiply the first equation by 2:
6x - 8y = -66
4x - 6y = -48
Subtract the second equation from the first:
2x = 18
x = 9
Substitute x back into the first equation:
4(9) - 6y = -48
36 - 6y = -48
-6y = -84
y = 14
Therefore, the solution to the system of equations is x = 9, y = 14.
3. Solve the system of two equations using elimination with multiplication.
4x - 6y = -48
-2x + 4y = 30
Multiply the second equation by 2 to eliminate x:
8x - 12y = -96
-2x + 4y = 30
Now, add the two equations:
8x - 12y + (-2x + 4y) = -96 + 30
6x - 8y = -66
Divide by 2 to simplify:
3x - 4y = -33
Now we have a new equation:
3x - 4y = -33
4x - 6y = -48
Multiply the first equation by 2:
6x - 8y = -66
4x - 6y = -48
Subtract the second equation from the first:
2x = 18
x = 9
Substitute x back into the first equation:
4(9) - 6y = -48
36 - 6y = -48
-6y = -84
y = 14
Therefore, the solution to the system of equations is x = 9, y = 14.
Wrong
Let's re-calculate the third problem using elimination with multiplication:
3. Solve the system of two equations using elimination with multiplication.
4x - 6y = -48
-2x + 4y = 30
First, simplify the equations to help in elimination:
-4x + 6y = 48
-2x + 4y = 30
Now, multiply the second equation by 2 to get the same coefficient for x (4x and -4x):
-4x + 8y = 60
Now, we have the following equations:
-4x + 6y = 48
-4x + 8y = 60
Subtract the first equation from the second equation to eliminate x:
2y = 12
y = 6
Substitute y back into one of the original equations:
4x - 6(6) = -48
4x - 36 = -48
4x = -12
x = -3
Therefore, the solution to the system of equations is x = -3, y = 6.
3. Solve the system of two equations using elimination with multiplication.
4x - 6y = -48
-2x + 4y = 30
First, simplify the equations to help in elimination:
-4x + 6y = 48
-2x + 4y = 30
Now, multiply the second equation by 2 to get the same coefficient for x (4x and -4x):
-4x + 8y = 60
Now, we have the following equations:
-4x + 6y = 48
-4x + 8y = 60
Subtract the first equation from the second equation to eliminate x:
2y = 12
y = 6
Substitute y back into one of the original equations:
4x - 6(6) = -48
4x - 36 = -48
4x = -12
x = -3
Therefore, the solution to the system of equations is x = -3, y = 6.
Number 4 is wrong
Let's re-calculate the fourth problem:
4. Solve the system of two equations.
3x - 4y = 40
5x - 5y = 55
We will use the elimination method to solve this system of equations.
First, let's multiply the first equation by 5 and the second equation by 4 to eliminate y:
15x - 20y = 200
20x - 20y = 220
Now, subtract the first equation from the second equation:
5x = 20
x = 4
Substitute x back into the first equation:
3(4) - 4y = 40
12 - 4y = 40
-4y = 28
y = -7
Therefore, the solution to the system of equations is x = 4, y = -7.
4. Solve the system of two equations.
3x - 4y = 40
5x - 5y = 55
We will use the elimination method to solve this system of equations.
First, let's multiply the first equation by 5 and the second equation by 4 to eliminate y:
15x - 20y = 200
20x - 20y = 220
Now, subtract the first equation from the second equation:
5x = 20
x = 4
Substitute x back into the first equation:
3(4) - 4y = 40
12 - 4y = 40
-4y = 28
y = -7
Therefore, the solution to the system of equations is x = 4, y = -7.